A CMOS-Based Terahertz Reconfigurable Reflectarray with Amplitude Control: Design and Validation - You Wu; Yongli Ren; Fan Yang; Shenheng Xu; Maokun Li (Applied Sciences)
Terahertz reconfigurable reflectarray antennas (RRAs) hold significant promise for next-generation wireless communication systems by enabling dynamic beam control to mitigate severe path loss at high frequencies. This work presents a Complementary Metal-Oxide-Semiconductor (CMOS)-based RRA for terahertz amplitude control using tunable split-ring resonators. First, a terahertz switch in standard 65 nm CMOS process is designed, tested, and calibrated on the chip to extract the equivalent impedance, enabling precise RRA element design. Next, a reconfigurable element architecture is presented through the co-design of a split-ring radiator, control line, and a single switch. Experimental characterization demonstrates that the fabricated RRA achieves 3 dB amplitude variation at 0.290 THz with <8.5 dB element loss under 0.8 V gate bias. The measured results validate that the proposed single-switch topology effectively balances reconfigurability and loss performance in the terahertz regime. The demonstrated CMOS-compatible RRA provides a scalable solution for real-time beamforming in terahertz communication systems.